The impact of lactation and gestational age on the composition of branched-chain fatty acids in human breast milk. Issue 3 (2nd March 2018) - Jie, Liang; Qi, Ce; Sun, Jin; Yu, Renqiang; Wang, Xiangyu; Korma, Sameh A.; Xiang, Jingying; Jin, Qingzhe; Akoh, Casimir C.; Xiao, Hang; Wang, Xingguo
Abstract : The main BCFAs in preterm breast milk were iso -14:0, iso -15:0, anteiso -15:0, iso -16:0, iso -17:0, and anteiso -17:0, which were low than that in term breast milk. They were mainly located in the sn-2 position of TAGs and concentration in colostrum. Abstract : Breast milk consumption reduces the incidence of necrotizing enterocolitis (NEC) in preterm infants compared to formula. Branched-chain fatty acids (BCFAs) are present in breast milk but not in most formulas intended for preterm infants. We aimed to determine the composition of BCFAs in the breast milk of mothers with preterm infants, and to understand the impact of gestational age at birth and stage of lactation on BCFA content. The main BCFAs in preterm breast milk were iso -14:0, iso -15:0, anteiso -15:0, iso -16:0, iso -17:0, and anteiso -17:0. Breast milk BCFAs as a percent of total fatty acids (g per 100 g, %) were significantly different across lactation stages, with the highest concentration in colostrum, followed by transitional and mature breast milk (median: 0.41, 0.31, and 0.28%, respectively, p < 0.05). Lower BCFAs in preterm breast milk compared to term breast milk may have been related to maternal intake, or the ability of the mammary gland to extract BCFA from plasma, or differences in mammary gland BCFA synthesis. BCFAs were mainly in the sn-2 position (52–65%), similar to palmitic acid. Overall, preterm and term breast milk BCFAs were similar and showed specific concentration patterns, resembling 16:0 with respect to sn-2 positional distribution. BCFAs were reduced with lactation stage, similar to highly unsaturated fatty acids.